Germination and seedling morphology of four South American Smilax (Smilacaceae). - Redondo Martins, Aline (Universidad de Costa Rica, 2012)
Species of Smilax, also known as greenbrier, are widely distributed in Brazil and their commercial trades are carried out by the extractivism of native species. We the aim to provide information about the germination and development of seedlings in four Smilax species, different experiments were developed under controlled conditions. We evaluated two germination treatments: temperature (30°C and 20-30°C) and light (presence/ absence), and for few cases the tetrazolium treatment was applied. A different treatment response was observed among the studied species. Light had a significant influence in S. brasiliensis, with the highest germination rates at 20-30°C in dark conditions. S. campestris showed significant differences among temperature treatments, but not to light; while S. cissoides showed high germination rates (66-78%), independently of treatment. However, S. polyantha had low germination rates (19-24%). After one year, the expanded leaves showed different characteristics among the studied species. Leaves of S. brasiliensis were ovate, coriaceous, three main veins and prickle-like structures only on the midrib on abaxial face. S. campestris leaves were oblong, coriaceous and prickle-like structures were located at the leaf midrib and margin. S. cissoides had ovate-elliptic, membranaceous leaves, with three main veins with prickle-like structures on the abaxial face. S. polyantha leaves showed ovateelliptic, coriaceous leaves, with three main veins, translucent secondary veins and no prickle-like structures. A seedling identification key was elaborated based on morphological characteristics.